The Role of Social Cohesion in Preventing Child Abuse Among Rural Chinese Left-Behind Children - Zhang, Huiping (Journal of interpersonal violence, 2022)
Child abuse is a significant public health issue that can affect children?s physical and mental health. However, few studies have examined rural Chinese left-behind children. The role of social cohesion of rural Chinese communities in the prevention of child abuse remains understudied. The present study aims to investigate certain factors that could reduce child abuse problems, placing a special focus on the protective role of social cohesion, especially for left-behind rural children. Data were collected from a sample of 1,049 school-aged rural children from the largest middle school in China?s Henan Province. It was found that social cohesion directly affected physical abuse and emotional abuse; furthermore, social cohesion was more significantly associated with emotional abuse, whereas sexual abuse was a more significant issue for left-behind children than for those living with their parents. However, the moderating effect of the left-behind status on the association between social cohesion and physical abuse was not significant. Our findings suggest that social cohesion is an important factor for preventing emotional and sexual abuse. Thus, it is necessary to enhance social cohesion in rural Chinese communities with left-behind children to reduce their risk of experiencing child abuse.